Epididymal sperm characteristics in Brown-throated Sloth (Bradypus variegatus Schinz, 1825) - Gustavo Oliveira Alves Pinto; José Henrique Alves Nascimento e Silva; Giovanna Isabella de Souza Couto; Lucas Facundo Moura Tobal; Fabricio Bezerra de Sá; Gustavo Ferrer Carneiro; Maria Madalena Pessoa Guerra; Gilcifran Prestes de Andrade (Theriogenology Wild)
Three-toed sloths (Bradypus variegatus) are mammals belonging to the superorder Xenarthra and are commonly found in the tropical forests of Latin America. Few studies have investigated aspects related to the reproduction of these animals, and there is a lack of research on the characteristics of their spermatozoa. This study aimed to evaluate spermatozoa recovered from the epididymides of four animals that were euthanized at CETRAS-Tangara in Recife, Brazil. Gamete recovery was successful in only two individuals, leading to histological analyses of the gonads and epididymides. The absence of gametes, combined with histological findings and the topographical position of the gonads, confirmed that partial testicular descent is necessary for the initiation of spermatogenesis in this species. The recovered gametes exhibited low motility (18.8 %) and poor acrosomal integrity (8 %). Despite these results, this investigation provided initial insights into the spermatozoa of B. variegatus, which may contribute to future research aimed at studying and preserving Bradypus species.